Experimental Study on Characteristics of A New Cryopreservation Apparatus - Yang Ge Zhang Shaozhi Chen Guangming Yu Xiaoyi Wu Dongbo (Zhileng xuebao)
The authors developed a new cryopreservation apparatus for the long-term preservation of biomaterials which incorporates auto-cascade refrigeration,automatic control and the liquidus-tracking method.The experiments for cooling and warming with variable concentration were conducted under the control of programs with three common cryoprotectants separately including glycerol,propylene glycol and dimethyl sulfoxide.The final solution concentration arrived at the critical concentration for vitrification and the...